The use of regenerative techniques in apical surgery: A literature review - Thomas von Arx; Mohammed AlSaeed (Saudi Dental Journal)
Apical surgery has become a standard of care for tooth maintenance if conventional endodontic retreatment is not possible or associated with risks. However, in certain situations, the outcome of apical surgery may be compromised due to the extent or location of the periapical or periradicular lesions. The present review article including clinical and experimental studies reports and discusses the outcome of regenerative techniques (RT) in conjunction with apical surgery, with regard to the type of periradicular lesions: Apical lesions: The majority of studies have shown no benefit for healing in test sites treated with RT compared to control sites treated without RT. The use of a radio-opaque bone filler/substitute may even compound the radiographic interpretation of periapical healing. Currently, the use of RT for lesions <10 mm limited to the apical area is not warranted. Through-and-through lesions: All reviewed studies demonstrated a better outcome for test sites with RT compared to the control sites without RT; hence the use of RT for treatment of tunnel lesions in apical surgery is recommended. Apico-marginal lesions: All clinical studies assessed cohorts without controls, and, therefore, no firm conclusion about the benefit of RT for treatment of apico-marginal lesions in conjunction with apical surgery can be drawn. However, the experimental animal studies have shown that healing of teeth with apico-marginal lesions appears to benefit from RT. Keywords: Apical surgery, Regenerative technique, Bone regeneration, Bone defect